Seizures and Epilepsy in Sotos Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Clinicians from the Child Neurology Division, Sapienza University of Rome, and 7 other pediatric neurology centers in Italy report a series of 19 Sotos syndrome (SS) patients with febrile seizures (FS) and/or epilepsy during childhood and a long-term follow-up.